Digital humanities in pedagogical education: trends and prospects for the development of project activities (Journal of Educational Sciences, 2025)
This study examines the application of digital research in the humanities within teacher education. The article discusses the prerequisites for the emergence of the Digital Humanities direction and fundamental research in this area. The relevance of digital research in the humanities is substantiated, based on the processes of globalization and digitalization in the field of education in the Republic of Kazakhstan. The article covers various aspects of the use of digital tools and resources to optimize learning and increase the effectiveness of teaching activities, examines examples of successful implementation of Digital Humanities projects in teaching practice, and explores potential areas of application of these technologies in the future. The main idea of the study is the use of digital humanities methods in teacher education, which helps modern teachers to be more effective and adapt to the changing requirements of the educational environment. The relevance of the undertaken research is justified by the increased interest of the modern scientific community in the use of digital tools in humanities research. This is evidenced by a large number of scientific publications devoted to innovative digital approaches to the analysis and interpretation of a literary work. The results of the study present the possibilities of using Digital Humanities methods in the educational trajectory: development of digital skills, analysis of large amounts of data, personalized learning, collaboration and knowledge exchange, development of critical thinking. 500 school teachers in Kazakhstan were surveyed. The author of the study envisions project technologies as the main form of work with Digital Humanities, allowing students to develop critical thinking, analytical thinking and the ability to self-organize in scientific research activities. The article is intended to expand readers' understanding of the possibilities of Digital Humanities in the context of teacher education and stimulate further research and application of modern digital technologies in the educational process.Key words: Digital Humanities, teacher education, project technologies, digital opportunities in education, digital humanities research, timeline, interdisciplinary approach.